Advance program of the First Asian Control Conference, ASCC, July 27 - 30 1994, Tokyo - Asian Control Conference (1st : 1994 : Tokyo); The Steering Committee of Asian Control Conference (ASCC); Society of Instrument and Control Engineers (Japan) (Tokyo : ASCC, 1994)
06